THE IMPLEMENTATION OF SHARIA MARKETING TO INCREASE CUSTOMER SATISFACTION AT MUAMALAT BANK OF BANTUL BRANCH OFFICE - Istiqomah Istiqomah; Richa Angkita Mulyawisdawati; Meriyati Meriyati (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2021)
The development of Syariah banking in Indonesia was marked by the establishment of Syariah Banking in all parts of the region. However, it cannot be denied that many people think that there is no difference between Islamic Banking and Conventional ones. This is a challenge for Syariah Banks in Indonesia, including Bank Muamalat Indonesia, namely the first pure Syariah Bank which was established in 1991 in retaining customers through business undertaken an effort to provide customer satisfaction by products and services offered. This study aims to identify how the implementation of Syariah Marketing Characteristics and principles of the Muamalat Bank of Bantul Branch Office. This Research is a descriptive-analytic study using a qualitative approach. The data was obtained through an interview process with the Marketing Manager and direct observation of the research object. The results showed that both the characteristics and principles of Syariah Marketing had been implemented as a whole by the Branch Office of the Muamalat Bank of Bantul Branch Office in all aspects of marketing performance. Keywords: Syari'ah Marketing, Satisfaction, Customer, Bank Muamalat Indonesia